2012
DOI: 10.1128/mbio.00266-12
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Blinded Analysis Indicates No Association between Chronic Fatigue Syndrome/Myalgic Encephalomyelitis and either Xenotropic Murine Leukemia Virus-Related Virus or Polytropic Murine Leukemia Virus

Abstract: The disabling disorder known as chronic fatigue syndrome or myalgic encephalomyelitis (CFS/ME) has been linked in two independent studies to infection with xenotropic murine leukemia virus-related virus (XMRV) and polytropic murine leukemia virus (pMLV). Although the associations were not confirmed in subsequent studies by other investigators, patients continue to question the consensus of the scientific community in rejecting the validity of the association. Here we report blinded analysis of peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 42 publications
2
57
0
5
Order By: Relevance
“…Furthermore, the absolute lack of XMRV in the various groups investigated herein challenges the results of previous studies that showed a high prevalence of XMRV in human populations and alleged an association with prostate cancer. This study supports the conclusions of studies that eventually led to the retraction of the original study reporting the association between XMRV and human diseases [19][20][21] .…”
Section: Ethical Considerationssupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, the absolute lack of XMRV in the various groups investigated herein challenges the results of previous studies that showed a high prevalence of XMRV in human populations and alleged an association with prostate cancer. This study supports the conclusions of studies that eventually led to the retraction of the original study reporting the association between XMRV and human diseases [19][20][21] .…”
Section: Ethical Considerationssupporting
confidence: 74%
“…The present available data led to the retraction of the original data reporting an association between XMRV and human diseases [19][20][21] . A wide variety of infectious agents, many of which are capable of infecting humans, are endemic to the Brazilian Amazon.…”
Section: Methodsmentioning
confidence: 99%
“…Even though they provided strong evidence for this hypothesis, subsequent studies failed to reproduce these results. [31][32][33] Lo et al studied the role of another virus, murine leukemia virus (MLV), in CFS. 34 They detected the virus in 32 of 37 CFS patients (86.5%) compared with only 3 of 44 (6.8%) healthy volunteer blood donors.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Funnet har senere vist seg å skyldes et laboratorievirus, og forskning i ettertid har konkludert med at det ikke finnes noen holdepunkter for at XMRV kan utløse CFS/ME (21) .…”
Section: Utløsende Faktorerunclassified